Mesomeric Effects of Azobenzene Bearing Natural Product-Based Molecules for Liquid Crystal Materials: An Overview - Saba, Farooq; Zainab, Ngaini (Bentham Science Publishers, 2020)
Latest progress in liquid crystal (LC) field related to azo molecules incorporated to natural product-based moieties for the improvement of LC texture and mesomeric phases has received great interest among researchers. LC containing natural product-based moieties i.e. menthol, kojic acid, cholesterol and chalcone with stable azo and azobenzene scaffolds with specific optical tunability has been widely reported for photo-active materials such as Liquid Crystal Display (LCD), LC films, smart windows and other devices. This review discusses on the influence of azobenzene, a renowned photo responsive and stable LC scaffold, in mesogenic phases due to photo-isomerization and optical switching. The incorporation of mesomeric phases natural product moieties to azo molecules has improved the properties of LC i.e from nematic phase to smectic phase with proper magnetic field alignment. Natural product-based LC can be useful in numerous applications especially practical electronic or optic devices i.e. optical image storage, display devices, solar cells, optical switching.